ANÁLISE DAS ESTRATÉGIAS DE GERENCIAMENTO DE RISCO NO TRABALHO DOS PROFISSIONAIS DA SAÚDE EM UM CAPS | Analysis of management strategies of risk at work of health professionals in a CAPS (Trabalho & Educação, 2017)
Studies show that the constraints faced by health workers has led to a significant increase in the disease of these professionals. Besides the presence of visible risks in the workplace, professionals also deal with unforeseen situations. In this context, the invisibility is configured as an arduous process, but necessary to manage the risks and promote health and safety in the work environment. The purpose of the study, the exploratory, is to survey the working conditions for professionals in a Psychosocial Care Center (CAPS), in order to understand the activity of these and identify the strategies used by these professionals to manage physical violence and psychic gifts in this context. The methodological approach of this study was based on Ergonomic Work Analysis (EWA), with the participation of 16 health professionals, including effective and contractors. The results showed that the disagreement between the proposed new model implemented in the sector, proposed by the Psychiatric Reform, and the deconstruction of the former, has contributed to generate impacts on the health of workers, since the strategies - individual and collective - to manage risks run through by the complexity of the psychiatric patient care service. ___Estudos apontam que os constrangimentos enfrentados em situação de trabalho, pelos trabalhadores da saúde, têm levado a um expressivo aumento no adoecimento desses profissionais. Além da presença dos riscos visíveis no ambiente de trabalho, os profissionais ainda lidam com situações não previstas. Nesse contexto, a invisibilidade configura-se como um processo árduo, mas necessário para gerir os riscos e promover saúde e segurança no ambiente laboral. O objetivo do estudo, do tipo exploratório, é fazer um levantamento das condições de trabalho dos profissionais de um Centro de Atenção Psicossocial (CAPS), de modo a compreender a atividade dos mesmos e identificar as estratégias utilizadas por esses profissionais para gerir a violência física e psíquica presentes nesse cenário. A abordagem metodológica deste estudo foi baseada na Análise Ergonômica do Trabalho (AET), como propedêutica, e na Análise Ergológica, no aprofundamento epistemológico, com a participação de 16 profissionais da saúde, entre efetivos e contratados. Os resultados revelaram que o desacordo entre a proposta do novo modelo implantado no setor, proposto pela Reforma Psiquiátrica, e a desconstrução do antigo tem contribuído para gerar impactos na saúde dos trabalhadores, uma vez que as estratégias - individuais e coletivas - para gerenciar os riscos perpassam pela complexidade do serviço de assistência ao paciente psiquiátrico.